Photosynthetic activity in the mature leaves of Sorghum bicolor as influenced by growth retardants - Sudhakara Rao, G.; Malakondaiah, N.; Rao, J.V.S. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Photosynthetic activity was measured in leaves of Sorghum bicolor 'Texas 414 treated with the growth retardants CCC, Alar, and Phosphon-D. The growth retardants increased leaf fresh weight and chlorophyll content by about 10 percent. The Hill reaction and non-cyclic photophosphorylation activities showed a significant increase of about 50 percent, while the cyclic type was stimulated by only 10 percent. Labeled carbon incorporation was stimulated by 25 percent with CCC. It is suggested that growth retardants may influence photosynthesis by promoting Photosystem II activity.